HUBUNGAN KETEBALAN SERASAH DENGAN KEPADATAN CACING TANAH DI KAWASAN ARBORETUM UNIVERSITAS RIAU SEBAGAI RANCANGAN MODUL PEMBELAJARAN BIOLOGI SMA KONSEP EKOSISTEM - Silaban, Maya Ismay; Suwondo, Suwondo; Suzanti, Fitra (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The aim of this research was to determine the relationship of litter thickness with earthworm density in the arboretum area university of riau. The research conducted on November 2018 until January 2019 with a survey method. The determining sampling area based on environmental topography, purposive random sampling with six stations where each station consisted of a 10x10 m plot with a 25x 25 cm plot sampling. Sampel is done by hand sortir method. Measured parametersinclude composition of thetype of earthworm, thickness of litter, density of earthworms, and the relationship of thickness of litter with density of earthworms. The research results found four types of species the highest Pheretima posthuma, Lumbricus rubellus, Pontoscolex corethrurus, and Periyonix excavatus. Density of earthworms was obtained at station VI of 50.6 ind /m2 with thickness of 6.3 cm litter and the lowest density obtained at station I of 16.6 ind / m2. There is a strong relationship with the value of the correlation coefficient (r) = 0.86 and value (R2) = 0.746. The results of the study can be used to design the Biology Learning module for senior high school concept ecosystem.Key Words: Composition of Earthworms, Thickness of Litter, Densitiy of earthworms, Arboretum University of Riau.